Barriers to Generating International Income: Evidence from the Business Operations Survey - Lynda Sanderson (New Zealand Government, The Treasury, 2016)
This note draws out data from the International Engagement module of the Business Operations Survey 2011. The module was designed to capture information on the international activities of a large, representative sample of New Zealand firms, including the types of activities they are involved in and the barriers they encounter. The note focuses on the level of interest that firms show in becoming internationally engaged, and how the barriers they perceive in entering and maintaining a place in international markets differ by their level of interest and experience. It also considers the extent to which interest in overseas income as reported in both the 2007 and the 2011 International Engagement modules translates to export market entry in later years, and how future entry propensity differs according to the barriers, motivations and strategies reported by the firm.
Keywords: D22; F10; 330; export barriers; firms; overseas income; international engagement; Handelshemmnisse; Absatz; Multinationales Unternehmen; Neuseeland